Effects of Walking Direction and Cognitive Challenges on Gait in Persons with Multiple Sclerosis. (7th October 2013) - Wajda, Douglas A.; Sandroff, Brian M.; Pula, John H.; Motl, Robert W.; Sosnoff, Jacob J.
Abstract : Declines in walking performance are commonly seen when undergoing a concurrent cognitive task in persons with multiple sclerosis (MS). The purpose of this study was to determine the effect of walking direction and simultaneous cognitive task on the spatiotemporal gait parameters in persons with MS compared to healthy controls. Ten persons with MS (Median EDSS, 3.0) and ten healthy controls took part in this pilot study. Participants performed 4 walking trials at their self-selected comfortable pace. These trials included forward walking, forward walking with a cognitive task, backward walking, and backward walking with a cognitive task. Walking performance was indexed with measures of velocity, cadence, and stride length for each testing condition. The MS group walked slower with significantly reduced stride length compared to the control group. The novel observation of this investigation was that walking differences between persons with MS and healthy controls were greater during backward walking, and this effect was further highlighted during backward walking with added cognitive test. This raises the possibility that backward walking tests could be an effective way to examine walking difficulties in individuals with MS with relatively minimal walking impairment.